How to woo the smart ones? Evaluating the Determinates that particularly attract highly qualified people to cities. - Buch, Tanja; Hamann, Silke; Niebuhr, Annekatrin; Rossen, Anja (My University, 2014)
Human capital is a driving factor of innovation and economic growth. Economic prospects of cities depend on high qualified workers' knowledge and therefore, attracting highly qualified workers plays a fundamental role for cities' prospects. This study contributes to the question which factors primarily determine the mobility-decision of highly qualified workers by investigating the determinants of the migration balance of German cities between 2000 and 2010. Furthermore, it compares the effects of several labour- and amenity-related variables on migration rates of highly qualified workers and the remaining workforce. Findings suggest that local labour market conditions influence the mobility decision but amenities matter too for the high-skilled. The preferences of the highly qualified workers partly differ from those of the rest of the workforce. However, there are also several factors that do not show systematic differences across skill groups.
Keywords: Stadt; Standortfaktor; Zuzug; Arbeitsmarkt; Berufsqualifikation; Marketing; Stadtökonomie; Fachkraft